A Comparison of Substrate Utilization Profiles During Maximal and Submaximal Exercise Tests in Athletes - Ramadoss, Rohit; Stanzione, Joseph R.; Volpe, Stella Lucia (Frontiers in Psychology, 2022)
Background: Exercise is primarily sustained by energy derived from lipids and glucose. Substrate utilization is the pattern by which these fuel sources are used during activity. Objective: The objective of our study was to evaluate substrate utilization profiles during maximal and submaximal graded exercise tests, and to determine the extent to which body composition influences substrate utilization during the exercise tests. Methods: A total of 27 male athletes, 32.5 ± 11 years of age, were recruited for this study. Body composition was analyzed using a bioelectrical impedance analyzer. Maximal and submaximal exercise tests were performed on a treadmill. Results: Percent body fat (PBF) was 15.8 ± 5%. Maximal oxygen consumption (VO2max) was 47.6 ± 9 mL/kg/min, while percent VO2max at which participants were shifting to glucose predominance for energy during the maximal and submaximal tests were 76 ± 8.3% and 58.4 ± 21.1%, respectively. A paired-samples t-test was conducted to compare percent VO2max at crossover point in maximal and submaximal graded exercise tests. There was a significant difference in percent VO2max at the crossover point for maximal (76 ± 8.3%) and submaximal (58 ± 21.1%) tests (t=4.752, p=0.001). A linear regression was performed to elucidate the interaction between exercise intensity at the crossover point and body composition during a maximal and submaximal graded exercise test. There was a significant effect of PBF on percent VO2max at crossover point during the maximal graded exercise test (F (1,24)=9.10, P=0.006) with an R2 of 0.245. However, there was no significant effect of PBF on percent VO2max at crossover point during the submaximal graded exercise test (P>0.05). Conclusion: Substrate utilization, represented by the crossover point, is dependent on the rate of increase in exercise intensity. At maximal efforts, the crossover to carbohydrates from fats as the predominant fuel source occurs at a significantly later stage of percent VO2max than at submaximal efforts. Furthermore, body composition represented by PBF is a significant predictor of substrate utilization during maximal efforts. Athletes with a relatively higher PBF are more likely to have increased lipid oxidation during high intensity exercises than those with a lower body fat percentage.